Chipless RFID Based on RF Encoding Particle : Realization, Coding and Reading System. - Arnaud Vena; Etienne Perret; Smail Tedjini (Networks and telecommunications series., 2016)
Chipless RFID based on RF Encoding Particle: Realization, Coding and Reading System explores the field of chipless identification based on the RF Encoding Particle (REP). The book covers the possibility of collecting information remotely with RF waves (RFID) with totally passive tags without wire, batteries, and chips, and even printed on paper. Despite the many benefits of RFID, deployment is still hindered by several economic and technological factors. Among these barriers are the high cost of tags, lack of reliability and security in the information contained in the RFID chip, and how tags are 'recycled.' This book focuses on the development of chipless RFID tags, representing a new family of low cost tags. With this technology information is extracted from the electromagnetic response of the tag, which depends only on its geometry. Various solutions have been developed by the authors to increase the amount of information, reduce the surface of the tag, or improve the robustness of detection. Considerations such as realization using paper substrate, the development of a low cost detection system, and measurements in a real environment have been addressed for practical implementation.